Weakly Prime and Weakly Semiprime Fuzzy Ideals - Hadi, Inaam M A; Hamil, Maysoun A (Al-Nahrain Journal of Science, 2018)
In this paper we introduce the notion of weakly prime (weakly semiprime) fuzzy ideals of fuzzy ring as a generalization of weakly prime (weakly semiprime) ideals. We investiagate several characterizations and properties of these concepts.